Electronic Trading Platforms in Government Securities Markets : Background Note - World Bank (Washington, DC, 2016)
The objective of this background note is to provide some guidance to a Debt Management Office (DMO) seeking to launch an electronic trading platform in a government securities market, taking in consideration the experience gained by other DMOs abroad. Electronic trading platforms (ETPs) are one of the most important components in the organization of efficient secondary markets for government securities.